Residu b_{4,6}(n) terhadap modulo 2 dan 3 - Fadhlan Zhaahiran; Uha Isnaini (Journal of Mathematics UNP, 2023)
Integer partition is a branch of number theory that is still developing today. A partition of a positive integer n is a way to express   as a sum of positive integers without counting the order. Let   denote the number of partitions of  . We discover arithmetic properties of   which is the number of partitions of an integer n where the parts are not multiple by 4 or 6.